KI SAMIN SUROSENTIKO: THE STRUGGLE OF RATU ADIL 1889-1914 - Fadilla, Firza Azzam; Wijaya, Daya Negri; Sapto, Ari; Widiadi, Aditya Nugroho (JUPIIS: JURNAL PENDIDIKAN ILMU-ILMU SOSIAL, 2024)
The research topic in this study examines the role and autobiography of Ki Samin Surosentiko or Raden Kohar, who was a farmer who became a preacher and messiah in the saminism movement in the period 1889-1914. The teachings of Ageman Adam or Religions of Adam, the concepts of millenarianism, messianism were used to oppose the policy of tax payment and land tenure through the sikep resistance movement the Dutch East Indies Government in Central Java and East Java. This research is a historical research using historical research methodology so that this research aims to reveal historical facts from the perspective of the Dutch East Indies and saminism by using primary historical and newspapers as well as historical records of teaching saminism figures and using the approach of resistance theory and social resistance movement theory. The result of this research is, that Samin Surosentiko is a lineage of Javanese aristocrats who are considered to have charisma, magic, or sekti. Therefore, he is believed to be a messiah or Ratu Adil figure who is believed to bring salvation, revive the glory days of the indigenous people in the past, and can bring freedom from European colonialism. There is a fact that Saminism followers do not always carry out sikep resistance that prioritise the teachings and values preached by Samin Soerosentiko. There was one of the followers of Samin Soerosentiko, named Modongso who fought back with violence due to the arrest of Samin Surosentiko in 1907 by the Dutch East Indies Government.